Relationship between Czech and European developed stock markets: DCC MV GARCH analysis - Michael Princ (Charles University in Prague, Institute of Economic Studies (IES), 2010)
The study concentrates on an analysis of the Czech stock market performed by an application of DCC MV GARCH model of Engle (2002). Data sample including years from 1994 to 2009 is represented by daily returns of Prague Stock Exchange index and other 11 major stock indices. There is found an existence of increasing trend in conditional correlations among a whole European region. The trend reveals breakpoints splitting a data series into three phases of development. The analysis includes a composition of returns adjusted by exchange rates capturing a point of view of global investors. The Czech Koruna exchange rate effects in a conjunction with equity returns are identified as a possible risk aversion instrument. Granger causality concept is added in order to find a development of data flow directions in a perspective of the Czech market. Results show that unidirectional influence of foreign markets affecting Czech market occurs in data series.
Keywords: C32; E44; G14; G15; F36; 330; stock market integration; multivariate analysis; dynamic modelling; conditional correlation; Aktienmarkt; Aktienindex; Marktintegration; ARCH-Modell; Multivariate Analyse; Schätzung; Tschechische Republik; Welt